Factors that Influence Self-Efficacy in Maintaining Personal Hygiene of Postpartum Mothers - Magdalena Agu Yosali; Elpinaria Girsang; Tisna Yant; Siti Hanifatun Fajria (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: At present the health status of mothers and babies in Indonesia is still low, which is markedby high maternal mortality rate (MMR) and infant mortality rate (IMR). Mothers and families must be ableto carry out their roles and functions related to postnatal maternal health care and the health of their babies.Mother’s personal hygiene helps reduce the source of infection and increases the feeling of comfort in themother and thus increase the self-efficacy of postpartum mothers to care for their babies. The purpose ofthis study is to determine the direct and indirect influence of the role of health personnel, family support,physical conditions, sources of information and social environment to self-efficacy in postpartum mothersin maintaining personal hygiene at Pasir Mulya Health Center of Bogor City in 2017.Methods: This research study used cross-sectional design. The data collection with a total sample of 60participants was taken from questionnaires. The analysis method used was the Structural Equation Model(SEM) using SmartPLS 2.0.Conclusion: The self-efficacy variable of the postpartum mother in maintaining personal hygiene at PasirMulya Health Center of Bogor City was influenced by information source (2.61%), family support (6.39%),physical condition (31.62%), information source (39.40%) and social environment (24.72%). Total directand indirect influence of self-efficacy of postpartum mother in maintaining personal hygiene was 56.44%.Thestudy showed that when the mother received more information, then the self-efficacy will be higher. If apostpartum mother has high self-efficacy, the personal hygiene will improve as well and lower the maternaland infant mortality rate.